Lean blowout detection for bluff-body stabilized flame. (15th April 2020) - Chang, Liuyong; Cao, Zhang; Fu, Bo; Lin, Yuzhen; Xu, Lijun
Abstract: The present work proposed an index to extend the previous lean blowout detection method to bluff-body stabilized flame at the condition of low Reynolds number. Dynamic characteristics near lean blowout of low Reynolds number bluff-body flame are not exactly same with that of high Reynolds number bluff-body flame. Thus lean blowout detection index requires modification for low Reynolds number bluff-body flame. The flame images show that, for a fixed fuel flow, increase of air flow to a certain value can cause flame liftoff-reattachment events, and further increase of air flow can lead to complete liftoff and even lean blowout. Temporal and spectral analyses of the ion current and CH* signals exhibit that both standard deviation and low frequency energy within 0.2–10 Hz of each signal first increase due to flame liftoff-reattachment and then decrease due to complete flame liftoff with the increase of air flow. This leads to that the lean blowout detection indexes including the normalized root mean square (NRMS), normalized cumulative duration ( θ ) and fraction of the fast Fourier transform (FFT) power at low-frequencies ( F F T % [ 0 - f 1 H z ] ) first increase and then decrease with the increase of air flow. As a result, the flame at the liftoff state may be wrongly classified as stable state. To avoid this, the histogram distributions of two signals were investigated. The number of small value sample points of each signal increases with increase of air flow, indicating that the percentage of small value sample points can be used to detect lean blowout. The mean value of each signal at the liftoff-reattachment state is used as the threshold value to classify small value sample points. For either the ion current signal or CH* signal, percentage of sample points below the corresponding threshold value ( P < k ) is used to detect lean blowout. The flame is considered as close to lean blowout when P < k reaches 50%. Experimental results show that P < k can be used for reliable detection of lean blowout for bluff-body stabilized flame at the condition of low Reynolds number.